1985
DOI: 10.1007/bf01201802
|View full text |Cite
|
Sign up to set email alerts
|

Antisperm antibodies and in vitro fertilization failure

Abstract: A new enzyme-linked immunosorbent assay (ELISA)-based test (Zer, Jerusalem) has allowed us to show the presence of antisperm antibodies (1:32 to 1:64) in the blood of 14 (33%) of 32 patients undergoing in vitro fertilization and embryo transfer (IVF-ET) under gonadotropin stimulation. Observation of the morphology of fertilization in eight patients with and seven patients without antisperm antibodies has shown a significant association (P less than or equal to 0.025, Fisher exact probability test) among the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This finding was obtained by using the Zer ELISA antisperm antibody kit which is both sensitive and specific, as was demonstrated by the work of Harel and Nelken [11] and Pexieder and associates [12]. In a comparative study of 400 patients performed with the Zer ELISA antisperm antibody kit and a microscopic sperm agglutination test, the F-D method, it was found that antibodies detected by the microscopic method were also detected by ELISA.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This finding was obtained by using the Zer ELISA antisperm antibody kit which is both sensitive and specific, as was demonstrated by the work of Harel and Nelken [11] and Pexieder and associates [12]. In a comparative study of 400 patients performed with the Zer ELISA antisperm antibody kit and a microscopic sperm agglutination test, the F-D method, it was found that antibodies detected by the microscopic method were also detected by ELISA.…”
Section: Discussionmentioning
confidence: 57%
“…These were cases of unexplained oligospermia, ejaculates with agglutinated spermatozoa and bad motility and low viability of sperm [11]. Moreover, Pexieder and associates [12], using the Zer ELISA antisperm antibody kit, have shown a significant association (/9<0.025) among the cumulus/corona coagulation, the absence of fertilization, and the presence of antisperm antibodies in patients undergoing in vitro fertilization and embryo transfer. The increased frequency of antisperm antibodies in OC users could not be correlated to differences in genetic or socioeconomic status, since all the patients came from the same genetic and social backgrounds.…”
Section: Discussionmentioning
confidence: 97%
“…Whilst blood is the most convenient test fluid, the role of humoral antibodies in infertility is unclear. They have been reported to cause cumulus/corona coagulation resulting in failure to fertilize the oocyte, even in serumfree medium (Pexeider et al, 1985), though others have shown that fertilization is not affected if such antibodies are absent from the insemination medium (Yovich et al, 1984). A prospective study by Eggert-Kruse et al (1989) of 235 couples with infertility showed that such circulating antibodies do not influence the fertility prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in agreement with previous studies which reported that women with antisperm antibodies have several problems to overcome in order to achieve successful IVF-ET, such as a low fertilization rate and poor quality of transferred embryos 18 , so cumulus/oocyte complex washing and/or enzymatic cumulus removal are considered as elective interventions in the case of antisperm immunity. Each patient entering an IVF-ET program should have the antisperm antibody assay performed as a preliminary screening 19 . However, in another study a high implantation rate was observed in those with elevated ASA, even in women at advanced age.…”
Section: Correlation Of Follicular Fluid ( Crp) and (Asa) Levels And mentioning
confidence: 99%